1997
DOI: 10.1111/j.1469-7793.1997.347bh.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin Regulates Cyclic GMP‐Dependent Electrogenic Cl Secretion in Mouse Ileum In Vitro

Abstract: Basal electrogenic Cl− secretion, measured as the short‐circuit current (Isc), was variable in ileum removed from tetrahydrobiopterin (BH4)‐deficient hph‐1 mice and wild‐type controls in vitro, although values were not significantly different. The basal nitrite release and mucosal cyclic guanosine 3′,5′‐monophosphate (cyclic GMP) production were similar in control and BH4‐deficient ileum. Mucosally added Escherichia coli heat‐stable toxin (STa, 55 ng ml−1) increased the nitrite release, cyclic GMP levels and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Instillation of the nitric oxide synthase substrate l -arginine into the ileum also induced both ileal and jejunal secretion, but equivalent d -arginine did not alter fluid transport, indicating that the fluid secretion induced was not an osmotic effect. Recently, the nitric oxide (NO) synthase cofactor tetrahydrobiopterin was implicated in the regulation of electrogenic secretion stimulated by STa and l -arginine in the mouse ileum in vitro 9. This strongly suggests that NO is involved in intestinal secretion, and our present results show that NO is implicated in the activation of remote jejunal secretion.…”
Section: Discussionsupporting
confidence: 70%
“…Instillation of the nitric oxide synthase substrate l -arginine into the ileum also induced both ileal and jejunal secretion, but equivalent d -arginine did not alter fluid transport, indicating that the fluid secretion induced was not an osmotic effect. Recently, the nitric oxide (NO) synthase cofactor tetrahydrobiopterin was implicated in the regulation of electrogenic secretion stimulated by STa and l -arginine in the mouse ileum in vitro 9. This strongly suggests that NO is involved in intestinal secretion, and our present results show that NO is implicated in the activation of remote jejunal secretion.…”
Section: Discussionsupporting
confidence: 70%
“…The newborn hph-1 mice has been previously reported to have pyloric muscle hypertrophy (2), and reduced bowel tissue L-arginine-stimulated NO generation was documented in adult animals of this BH4-deficient strain (29). Together these findings suggest that the reduced gastric emptying in newborn hph-1 mice involves reduced NO-dependent pyloric relaxation.…”
Section: G54mentioning
confidence: 67%
“…We have previously reported on the lungs of the newborn hph-1 mice, where we documented a 30-fold lower tissue BH4 content when compared with wild-type control animals of similar age (4). The hph-1 mice tissue BH4 content increases with age through an unknown mechanism (8,9), and the adult hph-1 mice ileal tissue BH4 content is only threefold less than age-matched control animals (29).…”
Section: G50mentioning
confidence: 89%
“…In the isolated ileum of wild-type mice, L-arginine increased NO release, cyclic GMP production, and electrogenic Cl Ϫ secretion. However, these actions were reduced in tetrahydrobiopterin (BH 4 )-deficient hph-1 mice, suggesting that BH 4 might be a target for the modulation of electrogenic ion transport; this highlights the complexity of the interactions between NO and cyclic GMP in the gut (Rolfe et al, 1997). It has been reported that BH 4 is a critical factor in producing NO from L-arginine (Kwon et al, 1989), and BH 4 deficiency not only reduces the production of NO but also enhances superoxide generation (Pou et al, 1992;Shinozaki et al, 1999).…”
Section: Secretion and Neurogenic Nitric Oxidementioning
confidence: 99%